2007
DOI: 10.1007/s11671-007-9081-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for Applications in Cellular Imaging

Abstract: In the following review we discuss several types of nanoparticles (such as TiO2, quantum dots, and gold nanoparticles) and their impact on the ability to image biological components in fixed cells. The review also discusses factors influencing nanoparticle imaging and uptake in live cells in vitro. Due to their unique size-dependent properties nanoparticles offer numerous advantages over traditional dyes and proteins. For example, the photostability, narrow emission peak, and ability to rationally modify both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(113 citation statements)
references
References 124 publications
(179 reference statements)
4
108
0
1
Order By: Relevance
“…With our 6 nm nanoparticles we found loading of up to 630 Gd atoms per nanoparticle. Unlike larger nanoparticles, however (18), nanoconjugates used in this study are sufficiently small to be easily taken up by the cells, as shown. Nanoparticles in excess of 20 nm experience difficulties in cellular uptake (18), and the 130 nm nanoparticles coated with Gd may be expected to remain in the space between cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…With our 6 nm nanoparticles we found loading of up to 630 Gd atoms per nanoparticle. Unlike larger nanoparticles, however (18), nanoconjugates used in this study are sufficiently small to be easily taken up by the cells, as shown. Nanoparticles in excess of 20 nm experience difficulties in cellular uptake (18), and the 130 nm nanoparticles coated with Gd may be expected to remain in the space between cells.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike larger nanoparticles, however (18), nanoconjugates used in this study are sufficiently small to be easily taken up by the cells, as shown. Nanoparticles in excess of 20 nm experience difficulties in cellular uptake (18), and the 130 nm nanoparticles coated with Gd may be expected to remain in the space between cells. Furthermore, due to an oligonucleotide that recognized intracellular target, nanoconjugates described here are endowed with long intracellular retention times (16); while the CA agent used on its own shows minimal long-term tissue retention (20).…”
Section: Discussionmentioning
confidence: 96%
“…Gold nanoparticles (GNPs) were used as PA imaging contrast agents because they offer superior chemical stability and are used extensively in live cell imaging. 18,19 We first measured the pulse energy threshold that corresponded to the onset of photothermal bleaching of 120 pM, 70-nm-diameter colloidal GNPs. The laser beam was focused into the solution held in a silicone tube, and the PA signals were monitored over time to observe the potential photothermal bleaching.…”
Section: Resultsmentioning
confidence: 99%
“…The increased internalization into superficial cells of dysplastic urothelium in comparison to normal superficial cells reveals the potential that nanoparticles could be used in improved diagnostic and optimized treatment of urinary bladder cancer. 31,[48][49][50][51] However, the increased nanoparticle internalization is not an explicit property of the partially differentiated cells found in the neoplastically transformed urothelium, but is also seen in normal urothelial cells located next to the exfoliated regions of the urothelium. Therefore, the AuNPs above can all be used to follow endocytosis as well as be used as a sensitive marker of differentiation and functionality in urothelial cells.…”
Section: Discussionmentioning
confidence: 99%